Study on Waste Acid Modificated Industrial Solid Waste Aluminum Ash to Prepare Environmental Functional Materials to Remove Fluoride Ions in Wastewater - Ren, Yuanchuan; Chen, Xiuping; Qu, Guangfei; Wu, Fenghui; Yang, Yuyi; Wang, Zuoliang; Liu, Xinxin; Jin, Caiyue; Hu, Yan (Frontiers in Environmental Science, 2022)
C-SAAoa particles synthesized by simple and low-cost calcining industrial solid waste aluminium ash combined with waste oxalic acid modification process show excellent performance in fluoride removal speed and adsorption capacity. Their adsorption capacity on fluoride was determined at about 180.57 mg/g at pH 3.0, which was among the highest reported values in the literature. It was determined that the adsorption mechanism of fluoride on C-SAAoa particles followed mechanisms such as ion exchange, electrostatic action, and the surface - OH groups played a major role in the fluoride removal process. C-SAAoa particles can effectively remove fluoride, even in the presence of a certain concentration of competing anions. At the same time, the material possesses good cycling performance, and can still maintain 78.9% of the initial adsorption capacity in the longitudinal for eight recycles. Therefore, it may have the potential to become a promising adsorbent as a supplement to industrial solid waste resource-based utilization processes and also for fluoride removal in small-scale treatment facilities or wastewater with high fluoride concentrations.